Manganese‐Based Layered Double Hydroxide Nanoparticles as a T1‐MRI Contrast Agent with Ultrasensitive pH Response and High Relaxivity. Issue 29 (6th June 2017) - Li, Bei; Gu, Zi; Kurniawan, Nyoman; Chen, Weiyu; Xu, Zhi Ping
Abstract : Recently, Mn(II)‐containing nanoparticles have been explored widely as an attractive alternative to Gd(III)‐based T1 ‐weighted magnetic resonance imaging (MRI) contrast agents (CAs) for cancer diagnosis. However, as far as it is known, no Mn‐based MRI CAs have been reported to sensitively respond to a very weakly acidic environment (pH 6.5–7.0, i.e., the pH range in a tumor microenvironment) with satisfactory imaging performance. Here, recently devised pH‐ultrasensitive Mn‐based layered double hydroxide (Mn‐LDH) nanoparticles with superb longitudinal relaxivity (9.48 mm −1 s −1 at pH 5.0 and 6.82 mm −1 s −1 at pH 7.0 vs 1.16 mm −1 s −1 at pH 7.4) are reported, which may result from the unique microstructure of Mn ions in Mn‐LDH, as demonstrated by extended X‐ray absorption fine structure. Further in vivo imaging reveals that Mn‐LDH nanoparticles show clear MR imaging for tumor tissues in mice for 2 d post intravenous injection. Thus, this novel Mn‐doped LDH nanomaterial, together with already demonstrated capacity for drug and gene delivery, is a very potential theranostic agent for cancer diagnosis and treatment. Abstract : Novel Mn‐based layered double hydroxide (Mn‐LDH) nanoparticles show excellent magnetic resonance imaging capacity with outstanding pH‐ultrasensitivity at pH 7.4–6.5 and superb longitudinal relaxivity. These Mn‐LDH nanoparticles are able to clearly image tumor tissue for 2 d in vivo. Together with demonstrated capacity for drug and gene delivery, Mn‐LDH nanomaterials are potential theranostic agents for cancer treatment.